Urban Dynamics and Equity in Motion: Local Policies on Physical Activity. The Case of Cluj-Napoca, in the Light of International IMPAQT BPEs (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This study examines how local policies in Cluj-Napoca, Romania – a rapidly urbanising and economically dynamic city – promote physical activity (PA) through free-access sports infrastructure. It aims to understand how such initiatives reflect broader commitments to spatial justice, health equity, and inclusive urban development.Recent municipal investments – such as bike lane networks, free-access sports complexes, and public park fitness installations –reflect a growing political commitment to inclusive urban health. These interventions unfold in a highly privatised sports sector and raise questions about equity, accessibility, and the lived experience of these spaces by different social groups.Methods: Employing public policy evaluation tools combined with sociological analysis to assess municipal interventions such as bike lanes, free-access sports complexes, and public park fitness installations. The study analyses policy documents, governance frameworks, and urban planning practices and includes interviews with key stakeholders to evaluate how these measures address inequalities in access to PA infrastructure.Results: Preliminary findings reveal a mismatch between political intentions and on-the-ground access. While infrastructure has expanded, marginalised and lower-income populations report limited usability due to locational and design constraints. The city’s efforts are shaped by a highly privatised sports sector, which influences public accessibility. These findings contribute to the identification of national best practice exemplars (BPEs) under the IMPAQT framework.Conclusion: Cluj-Napoca illustrates the complexities of promoting equitable PA in contemporary urban settings. This sub-national level case study provides an understanding of BPEs, as a national benchmark, highlighting how local governments navigate the complexities of promoting physical activity in contemporary cities. It emphasises the importance of local policy analysis to understand how public spaces for PA are not only available but meaningfully accessible to all, including marginalised-less-visible groups.Support/Funding Source: project IMPAQT, funded from Ireland, Health Research Board; Poland, National Centre for Research and Development; Germany, Federal Ministry of Education and Research; The Netherlands, The Netherlands Organisation for Health Research and Development; Romania, Executive Agency for Higher Education, Research, Development and Innovation Funding; Lithuania, Research Council of Lithuania, under the umbrella of the Partnership Fostering, a European Research Area for Health (ERA4Health).